THE IMAGINARY OF FEAR IN THE CULTURAL SCENARIOS OF THE MAGIC TOWN “EL FUERTE”, SINALOA, MEXICO - Sotelo Amano, Celina Alejandra (Benemérita Universidad Autónoma de Puebla, 2020)
The following research aimed to evaluate the imaginary of fear configured in the cultural settingsin the Magic Town of El Fuerte, Sinaloa, proposing as main indicators the scenarios of fear(desolate, dark and deteriorated, etc.), stereotypes of fear, criminal events and perception of fearand insecurity. Understanding the imaginary of fear as: the construction of mental images thatevoke situations of violence and danger before the beliefof the possibility of being involved in them, whether or not it is a feasible situation.